Financial aid for the rehabilitation of individuals with spinal cord injuries in Bangladesh - Nahar, Nazmun; Nuri, Reshma Parvin; Mahmud, Ilias (© 2012 Asia Pacific Disability Rehabilitation Journal, 2017)
This article was published in the Asia Pacific Disability Rehabilitation Journal [ © 2012 Asia Pacific Disability Rehabilitation Journal ] and the definite version is available at : http://dx.doi.org/10.5463/DCID.v23i2.97 The Journal's website is at: http://dcidj.org/article/view/97